CP-121 Adverse drug reactions from antipsychotics contributing to admissions in an acute general hospital. (24th March 2015) - Brooks, J; Schneider, C; Wilson, K; Hashmi, M; Hebron, B
Abstract : Background: Antipsychotic medicines are associated with an increased risk of falls, delirium, cerebrovascular and cardiovascular fatalities. 1 These adverse drug reactions (ADRs) have a negative impact on patient quality of life and are often implicated in hospital admissions; as such they can be a significant burden on health services. 2 Purpose: To investigate how adverse drug reactions (ADRs) from antipsychotic medicines may contribute to admission in an acute general hospital. Material and methods: We undertook a prospective study of all patients in our institution who were prescribed antipsychotics. Patients were identified from real-time dispensing information which was used by a specialist pharmacist to drive a ward-based clinical pharmacy review. If an ADR was suspected, consent was gained and a referral to the liaison psychiatric team generated. Results were recorded in line with national [Caldicott] ethical guidelines. Results: During the study period (17/09/2012 to 28/10/2013), 312 patients prescribed antipsychotic medicines were admitted. Thirty-one patients (10%) were referred due to concerns over ADRs, the majority of which (24, 77%) were generated by the specialist pharmacist (figure 1). Following referral, 21 of the 31 patients had their antipsychotic drug altered. It was stopped in 11 patients and doses reduced in a further 10. Conclusion: An admission-related ADR was identified in 10% of the patients prescribed antipsychotic medicines. The pharmacist was pivotal in this process and detected the majority. Early identification and psychiatric referral is essential to facilitate a decision that balances the patients' mental and physical health needs. Pharmacists working in the acute sector should be mindful that antipsychotic medicines may contribute to admissions. A close relationship with psychiatric services can facilitate medicines review and prevent harm. References and/or Acknowledgements: BMJ Group and Pharmaceutical Press. British National Formulary; 68, 2014 Pirmohamed M, James S, Meakin S, et al . Adverse drug reactions as cause of admission to hospital: prospective analysis of 18, 820 patients. BMJ 2004;329(7456):15–19 No conflict of interest.